Role of Starting School Age in the Academic Performance at the Tertiary Level - Mahwish Ali Baber; Nawaz Ahmad (Journal of Education and Educational Development, 2017)
The purpose of this research was to find out whether starting school earlier than four years of age gave any academic benefit to the students in the long run. This research aimed to find out whether the students who started schooling earlier than four years of age are able to achieve better grades and are better at self-regulation at the tertiary level. For this purpose, a sample of 108 students from a private business school comprising both early and late school starters were made to fill in questionnaires reporting their school starting age, their CGPA and answering questions that showed their level of self-regulation. The findings of this study suggest that there is no difference in the academic performance of the two groups, both in terms of their CGPA and their self-regulation skills.